Bt rice could provide ecological resistance against nontarget planthoppers. Issue 10 (10th April 2018) - Wang, Xingyun; Liu, Qingsong; Meissle, Michael; Peng, Yufa; Wu, Kongming; Romeis, Jörg; Li, Yunhe
Summary: Genetically engineered (GE) rice lines expressing Lepidoptera‐active insecticidal cry genes from the bacterium Bacillus thuringiensis ( Bt ) have been developed in China. Field surveys indicated that Bt rice harbours fewer rice planthoppers than non‐ Bt rice although planthoppers are not sensitive to the produced Bt Cry proteins. The mechanisms underlying this phenomenon remain unknown. Here, we show that the low numbers of planthoppers on Bt rice are associated with reduced caterpillar damage. In laboratory and field‐cage experiments, the rice planthopper Nilapavata lugens had no feeding preference for undamaged Bt or non‐ Bt plants but exhibited a strong preference for caterpillar‐damaged plants whether Bt or non‐ Bt . Under open‐field conditions, rice planthoppers were more abundant on caterpillar‐damaged non‐ Bt rice than on neighbouring healthy Bt rice. GC–MS analyses showed that caterpillar damage induced the release of rice plant volatiles known to be attractive to planthoppers, and metabolome analyses revealed increased amino acid contents and reduced sterol contents known to benefit planthopper development. That Lepidoptera‐resistant Bt rice is less attractive to this important nontarget pest in the field is therefore a first example of ecological resistance of Bt plants to nontarget pests. Our findings suggest that non‐ Bt rice refuges established for delaying the development of Bt resistance may also act as a trap crop for N. lugens and possibly other planthoppers.